KAJIAN PENGGUNAAN BERBAGAI LEMPUNG TERAKTIVASI SEBAGAI ADSORBEN UNTUK MENURUNKAN KADAR AMONIA, NITRAT, DAN NITRIT DARI LIMBAH TAHU INDUSTRI - Maradang, Aksan Y; Mirzan, Moh; Prismawiryanti, Prismawiryanti (Univ. Tadulako, 2014)
Tofu industry liquid waste, which is still contains high concentration of organic materials, is one of the causes of pollution in environment. On the other hand, clay can be used as adsorbent and easily to be obtained. The aim of this study was to reduce ammonia, nitrate, and nitrite concentration on liquid waste of tofu industry using colected clay from three different locations at laboratory scale. Clay was collected from Kalukubula, Beka and Sibowi villages at Sigi District Central Sulawesi Province. Each clay was activated by 0.1 M HCl, 0.1 M NH4Cl or 0.1 M NaOH. The result showed that clay from Beka village has highest capacity to reduce nitrate, nitrite and ammonia concentration on liquid waste of tofu industry. Clay from Kalukubula village was better as absorbent than clay from Sibowi village. The strength of activator in increasing clay adsorptive was followed this order: NaOH < NH4Cl < HCl. Clay from Beka Village when activated by HCl 0.1 M, it could reduce 47.52%, 54.00% and 58.89% of amonia, nitrate and nitrite concentration, respectively.